Perception of quality of emergency rooms in services of state social enterprises second level of complexity in Risaralda (2019)
Currently, there is growing interest in assessing the perception of the qualityof medical services by patients and the public and private providers in theinternational context entities. By Law 100 of 1993, the overall operation of thesocial security system of health in Colombia was organized health. The present article is focused on the evaluation of health system and the hospitalemergency units. These, represent an important moment and decision ofcrucial incidence in life of the people demanding imperative medical assistance(emergencies). It concludes that in Colombia, support needed is available frominstitutions to give better operability conditions in the different instances.